Bipolar membrane/hydrophobic gas permeable membrane electrochemical systems for highly efficient removal of ammonium nitrogen in wastewater - YAN Zhang; KUANG Wenjie; JIANG Zhuwu; FENG Chunhua* (能源环境保护)
Ammonia nitrogen is one of the primary pollutants found in both surface water and groundwater, and its predominant form is heavily influenced by the pH of the aquatic environment. To address the pH dependency in the electrochemical oxidation and separation of ammonia nitrogen, we leveraged the advantages of a bipolar membrane (BPM) that stably generates H+/OH- in the electrolytic cell. Consequently, we proposed a bipolar membrane/hydrophobic gas permeable membrane-electrochemical system (BPM/GPM-EC) that demonstrated remarkable performance in removing ammonia nitrogen from wastewater. In a scenario where the initial ammonia nitrogen concentration was 4000 mg·L-1 and the current density was 10 mA·cm-2, operating the BPM/ GPM-EC system intermittently (with a focus on ammonia recovery) for 5 hours achieved an impressive 99.3% removal of ammonia nitrogen from the wastewater. Simultaneously, 92.3% of the ammonia nitrogen was successfully recovered, with a specific energy consumption of 18.2 kW·h·kg-1 N. In continuous-flow mode, the BPM/GPM-EC system achieved a remarkable ammonia recovery rate of 76.2% and completely removed ammonia nitrogen from the wastewater at a flow rate of 0.28 mL·min-1. Notably, the specific energy consumption forammonia nitrogen removal was only 14.9 kW·h·kg-1 N. These findings underscore the ability of BPM/ GPM-EC system to integrate low energy consumption and high efficiency in treating ammonia nitrogen in wastewater. The combination of recovery and removal presents a novel approach to address challenges associated with ammonia-containing wastewater treatment.